Pasture Aeration - Joao Vendramini; Maria Silveira (EDIS)
SS-AGR-321, a 2-page illustrated fact sheet by Joao Vendramini and Maria Silveira, presents the results of research conducted at the Range Cattle Research and Education Center in Ona to test the efficiency of aeration in increasing forage production on soils typical in Florida. Includes references. Published by the UF Department of Agronomy, May 2009.